School dietary habits & oral health experiences of primary school children in Johannesburg - Octavia Refiloe Lebele; Veerasamy Yengopal; Peedi Mathobela; Mpho Matlakale Molete (PLoS ONE, 2025)
Background & aim Understanding the impact of food exposures outside the home environment is pivotal for helping children establish healthy eating patterns, for the prevention and delay of dental caries and other non-communicable diseases. This study sought to assesses the dietary habits and oral health experiences of primary school children in Johannesburg. Methods This was a cross-sectional analytical study of grade three learners, aged 9–11 years old. The measurement tools used included an observational checklist, a questionnaire, an oral health examination and anthropometric measures for assessing the Body Mass Index (BMI). Correlation and regression analysis were undertaken to determine relationships between sugar intake, calories intake, dmft, DMFT and gingival index. Results Of the 107 eligible children participating, 68% were from a school with a feeding scheme and 31.8% with no feeding scheme. The mean (SD) of BMI, dmft, and DMFT were 18.19 (3.59), 3.14 (3.39), and 1.49 (2.10), respectively. The mean sugar content of meals served in schools with a feeding scheme was lower [11.65g (SD 9.6)] than the mean sugar content of food consumed at a schools with no feeding scheme [35.84g (29.9)]. The regression analysis in this population indicated that the low gingival score was associated with high BMI and sugar intake. Conclusion Although the sugar content of meals served at National School Nutrition Programme (NSNP) schools was less that the sugar content accessed by children at Non-NSNP schools, both the schools had poor controls over sugar consumption and purchasing behaviour of the learners. The low gingival score was attributed to socio-economic status and access to toothbrushes and pastes.